Spontaneous healing of lateral femoral cutaneous nerve injury and improved quality of life after total hip arthroplasty via a direct anterior approach - Yu Ozaki; Yasuhiro Homma; Tomonori Baba; Kei Sano; Asuka Desroches; Kazuo Kaneko (Journal of Orthopaedic Surgery, 2017)
Purpose: How the symptomatology of lateral femoral cutaneous nerve (LFCN) injury changes after total hip arthroplasty (THA) via direct anterior approach (DAA) is not known. Our hypothesis was that the symptoms of LFCN injury after THA via DAA in longer follow-up periods would resolve spontaneously, leading to an improved quality of life (QOL). The aims of this study were to investigate how the symptom LFCN injury changed after DAA–THA, and how those changes affected QOL. Methods: We investigated the incidence of LFCN injury after DAA–THA using self-reported questionnaires at two time points (initial survey: August 2014, present survey: August 2015). QOL was assessed by the Western Ontario and McMaster Universities Osteoarthritis Index, the Japanese Orthopaedic Association Hip Disease Evaluation Questionnaire, and the Forgotten Joint Score-12 (FJS-12). Types (dysesthesia or hypesthesia) and changes of the symptom were surveyed. Results: About 122 hips at average12.8 months postoperatively (initial survey), and of those, 89 hips at average 26.2 months postoperatively (present survey) were analyzed. The incidence of LFCN injury decreased significantly, from 31.9% to 11.2% ( p < 0.001). Spontaneous improvement of symptoms was seen in 96%. The difference of FJS-12 between patients with and without LFCN injury at the initial survey disappeared at the present survey. The dysesthesia group showed significant correlations between rate of improvement in LFCN injury and increase of QOL. Conclusion: Most symptoms of LFCN injury resolved spontaneously with longer follow-up periods. In particular, improvement of dysesthesia as a symptom of LFCN injury was associated with better QOL.